Dental Hygiene Faculty Calibration Using Two Accepted Standards for Calculus Detection: A Pilot Study. Issue 8 (1st August 2016) - Santiago, Lisa J.; Freudenthal, Jacqueline J.; Peterson, Teri; Bowen, Denise M.
Abstract : Faculty calibration studies for calculus detection use two different standards for examiner evaluation, yet the only therapeutic modality that can be used for nonsurgical periodontal treatment is scaling/root debridement or planing. In this study, a pretest‐posttest design was used to assess the feasibility of faculty calibration for calculus detection using two accepted standards: that established by the Central Regional Dental Testing Service, Inc. (CRDTS; readily detectible calculus) and the gold standard for scaling/root debridement (root roughness). Four clinical dental hygiene faculty members out of five possible participants at Halifax Community College agreed to participate. The participants explored calculus on the 16 assigned teeth (64 surfaces) of four patients. Calculus detection scores were calculated before and after training. Kappa averages using CRDTS criteria were 0.561 at pretest and 0.631 at posttest. Kappa scores using the scaling/root debridement or planing standard were 0.152 at pretest and 0.271 at posttest. The scores indicated improvement from moderate (Kappa=0.41–0.60) to substantial agreement (Kappa=0.61–0.80) following training using the CRDTS standard. Although this result differed qualitatively and Kappas were significantly different from 0, the differences for pre‐ to post‐Kappas for patient‐rater dyads using CRDTS were not statistically significant (p=0.778). There was no difference (p=0.913) in Kappa scores pre‐ to post‐training using the scaling/root debridement standard. Despite the small number of participants in this study, the results indicated that training to improve interrater reliability to substantial agreement was feasible using the CRDTS standard but not using the gold standard. The difference may have been due to greater difficulty in attaining agreement regarding root roughness. Future studies should include multiple training sessions with patients using the same standard for scaling/root debridement used for evaluation of students.